An Introduction to Ethical Questions Around Animal Research. (23rd August 2021) - Shriver, Adam J; Hutchison, Eric
Abstract: The principal investigator is an expert on the topic under investigation. The veterinarian is an expert in the health and wellness of an animal. But what, exactly, can ethicists add to discussions about animal research? This special issue of the ILAR Journal considers how contemporary ethics scholarship can be relevant to animal research. The articles were selected to highlight how clear thinking about values and the implications of those values can inform which research is conducted and how it is conducted.